Transforming Islamic Education in the Era of Industrial Revolutions 4.0 and 5.0: Challenges and Strategies - Ismaiza Busti; Refinal; Tamrin Kamal; Sri Wahyuni; Rosniati Hakim; Shikdar Mohammad Riazul (Walidem Institute and Publishing, 2026)
Objective: This study aims to analyze the overall transformation of Islamic education in responding to the challenges and opportunities that arise due to the Industrial Revolution 4.0 and the Industrial Revolution 5.0. Theoretical framework: This study is based on the theoretical framework of Human-Centered Technological Integration and Islamic Philosophy of Education. These two frameworks emphasize the importance of adapting Islamic educational institutions to digital disruption while maintaining spiritual and ethical values as the core of education. Literature review: A literature review shows that there is a widening digital divide among Islamic educational institutions, especially between traditional Islamic boarding schools and modern madrasas. Previous studies indicate that the integration of technologies such as artificial intelligence (AI), virtual reality (VR), and digital content in Islamic curricula is still very limited. In addition, there are concerns about moral degradation and the spread of radical content in the digital space, which has not been balanced with adequate digital literacy. Methods: This study uses a qualitative-descriptive approach with document analysis, policy analysis, and synthesis of the latest empirical data from UNESCO, the Ministry of Religion of the Republic of Indonesia, and independent studies on Islamic education. The data are thematically analyzed to identify systemic challenges and relevant transformation strategies. Result: The results of the study revealed four main problems, namely: (1) the limitations of digital infrastructure in Islamic boarding schools and madrasas; (2) a curriculum that has not been integrated with the field of STEM and digital ethical values; (3) the low digital competence of educators; and (4) the erosion of spiritual values due to learning models that rely too much on artificial intelligence and technology. However, there is a great opportunity for innovation through the development of integrative curricula such as digital fiqh and AI-based Sufism, the application of hybrid learning, and the use of financial technology (fintech) for waqf-based education funding. Implications: This study recommends accelerating the digitalization of Islamic education, technology-based curriculum reform, and improving educators' digital competencies, while maintaining a balance between innovation and Islamic values. Novelty: This study offers an integrative model that combines Islamic epistemology with the Industrial Revolution 4.0 and 5.0 paradigms to realize sustainable, ethical, and contextual Islamic education.